IMPLEMENTATION OF PROJECT BASED LEARNING BASED ON SCIENCE, TECHNOLOGY, ENGINEERING, AND MATHEMATICS (STEM) IN CALCULATING BACTERIAL POPULATION GROWTH - Sartika, Ika; Fuadaturrahmah (Jurnal Pelita Pendidikan, 2025)
This study aims to explore the implementation of project based learning (PjBL) based on Science, Technology, Engineering, and Mathematics (STEM) in calculating bacterial population growth. The research was conducted using a classroom action research (CAR) design with students of Parulian Senior High School as participants. Through the PjBL – STEM approach, students were angaged in project activities that entegrated biological concepts of bacterial growth with mathematical models, particularly exponential and logistic growth equations. Data were collected through observations, tests, and student project reports, then analyzed descriptively. The results showed that the implementation of PjBL-STEM improved students’ understanding of bacterial growth concepts, enhanced their ability to apply mathematical calculations in biological contexts, and fostered collaboration and problem-solving skills. This study demonstrates that integrating STEM-based project learning into biology classes effectively enhances students’ conceptual mastery and critical thinking.